Immunomodulatory properties of human dental pulp stromal cells: the role of IL-6/JAK/STAT3 pathway and PD-L1 - Di Tinco, Rosanna; Pisciotta, Alessandra; Bertani, Giulia; Orlandi, Giulia; Bertoni, Laura; Pignatti, Elisa; Bonacini, Martina; Rossi, Alessandro; Roelofs, Anke J.; Croci, Stefania; De Bari, Cosimo; Salvarani, Carlo; et al. (Frontiers in Immunology, 2026)
IntroductionHuman Dental Pulp Stromal Cells (hDPSCs) of neural-ectodermal origin hold immunomodulatory properties which make them a source for MSC-based therapies for the treatment of autoimmune diseases.MethodsIn this study hDPSCs were exposed to inflammatory conditions mimicked by co-culture with Peripheral Blood Mononuclear Cells activated with anti-CD3/CD28 (aPBMCs) or treatment with Conditioned Medium (CM) from aPBMCs with or without the addition of a specific IL6 receptor (IL6R) inhibitor. To assess IL-6 effects on PD-L1 expression, hDPSCs were treated with IL-6/sIL6R complex and the activation of IL-6 trans-signalling was investigated. The functional role of IL-6 in modulating PD-L1 protein stability was further confirmed by treating hDPSCs with a proteasome inhibitor.ResultsOur results highlighted that hDPSCs exposed to different inflammatory conditions activate Fas/FasL and PD1/PD-L1 pathways. Moreover, hDPSCs modulate inflammatory cytokines release of aPBMCs from Rheumatoid Arthritis (RA) patients. However, the inflammatory milieu induced the upregulation of IL-6 by hDPSCs, which was demonstrated to be strongly correlated to PD-L1 expression, suggesting its involvement in supporting their immunoregulation. Our data demonstrated that the activation of the IL6/JAK/STAT3 trans-signaling pathway in hDPSCs through stimulation with the IL6/sIL6R complex leads to an increase in PD-L1 protein levels, but not PD-L2, via proteasome inhibition.ConclusionOur study demonstrates the activation of the IL-6/PD-L1 axis in response to inflammatory conditions and underscores its potential significance in autoimmune diseases since a dysfunction of this mechanism could lead to the onset and progression of chronic inflammatory disorders.